Validity of Self-Reports Provided by People With Autism Spectrum Disorder Without Intellectual Disability: A Meta-Analysis - Danés, Marta; Botella, Juan; Belinchón, Mercedes (Anales de Psicología / Annals of Psychology, 2023)
Background: Literature collects that people with Autism Spectrum Disorder without Intellectual Disability (ASD-noID) frequently suffer co-occurring clinical problems that predict poorer adult outcome and reduce quality of life (QoL). Previous studies pose doubts about their capacity to recognize and communicate these problems, but that is an issue that, although relevant, has not yet been systematically revised. Method: A meta-analysis on 32 studies (1422 pairs of participants) was carried out to assess to what extent self-reports provided by people with ASD-noID match those provided by their parents. The articles were categorized according to the domains assessed and method. Results: Significant differences between self- and hetero-reports were found in the domains of Depression, QoL and Social skills (d= 0.406; -0.399 and -0.683, respectively), but not in Anxiety and Social anxiety. The average degree of agreement between both groups of reports was r = .40. Conclusions: Self- and hetero-reports do not provide interchangeable results on the problems of people with ASD-noID. However, a general inability to validate self-reporting cannot be attributed to them. Deeper analysis is necessary to allow to optimize the use of self-reports in this population with both clinical and research purposes.